Undersökning av radiogalaxer i kartläggningen XXL-North - Nilsson, Andreas; Krook, Christoffer; Tolliner, Lukas; Karlsson, Frida (My University, 2017)
This report aims at investigating two newly discovered radio galaxies in a 47 deg2 region of the sky labeled XXL-North. In the first step, a sensitive, high angular resolution radio map obtained with the Giant Meterwave Radio Telescope in India is scanned for interesting radio galaxies; in the second step, two of the found radio galaxies are analyzed in detail and additional data at radio frequencies and in other parts of the electromagnetic spectrum (X-ray, optical) are used. The spectral flux densities, spectral indices and spectral luminosities of the two radio galaxies are computed and related to their morphology. The host galaxies are identified and their redshifts and distances are established. Both have the same redshift z ' 0.14. The extents of the radio structures are, respectively, 35300 and 18000, which amounts to projected sizes of 850 kpc and 439 kpc, respectively. The derived luminosities are, respectively, (1.27 ± 0.13) · 1025 W Hz−1 and (6.30 ± 0.63) · 1024 W Hz−1. These are reasonable luminosity values for radio galaxies of morphological class FR II. Their structural appearance, with lobes containing distinct hot spots, supports this classification.
Keywords: Astronomi, astrofysik och kosmologi; Extragalaktisk astronomi; Astronomy, Astrophysics and Cosmology; Extragalactical astronomy